2019
DOI: 10.1097/mao.0000000000002315
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Suppression Effect of Hearing Aids in Patients With High-frequency Hearing Loss: A Randomized Double-blind Controlled Trial

Abstract: Introduction: Hearing aids (HAs) with frequency lowering have been used for high-frequency hearing loss (HFHL), but their effects on tinnitus relief have not been studied extensively. This randomized double-blind trial was performed to investigate and compare tinnitus suppression effects of conventional type HAs and frequency-lowering HAs in patients with HFHL. Methods: A total of 114 patients were randomized into three groups: conventional HA using wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…In summary, out of the 16 studies described above, nine studies showed significant improvements in tinnitus perception (Araujo and Iório 2016; Cabral et al 2016; Haab et al 2019; Hodgson et al 2015; Shekhawat et al 2014; Yakunina et al 2019; Yokota et al 2020; Zarenoe et al 2017; Zarenoe et al 2016), while four studies did not report significant tinnitus relief (Marcrum et al 2020; McNeill et al 2012; Peltier et al 2012; Strauss et al 2015). The other three studies did not test whether hearing aids’ use leads to tinnitus relief (Andersson et al 2011; Shekhawat, Searchfield, Kobayashi, et al 2013; Shetty and Pottackal 2019).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In summary, out of the 16 studies described above, nine studies showed significant improvements in tinnitus perception (Araujo and Iório 2016; Cabral et al 2016; Haab et al 2019; Hodgson et al 2015; Shekhawat et al 2014; Yakunina et al 2019; Yokota et al 2020; Zarenoe et al 2017; Zarenoe et al 2016), while four studies did not report significant tinnitus relief (Marcrum et al 2020; McNeill et al 2012; Peltier et al 2012; Strauss et al 2015). The other three studies did not test whether hearing aids’ use leads to tinnitus relief (Andersson et al 2011; Shekhawat, Searchfield, Kobayashi, et al 2013; Shetty and Pottackal 2019).…”
Section: Resultsmentioning
confidence: 91%
“…It is important to note that every patient also received one counselling session. More recently, Frequency Translation (FT), LFT and WDRC were compared in a randomized double-blind controlled trial by Yakunina et al (2019). A total of 94 tinnitus patients were randomized into the three groups and wore the hearing aid for three months, followed by a period of cessation for 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…According to the presumed neurological mechanisms of tinnitus, it can be hypothesized that hearing aids decrease afferent inhibition through sound enrichment in the central auditory system and thus achieve the goal of modulating neuroplastic changes. A study compared the effect on tinnitus between conventional hearing aids and frequency-lowering hearing aids in high-frequency hearing loss patients, and both groups found improvement in the quality of life [69]. Another study reported that spectrally notched hearing aids were more effective than unmodified hearing aids in treating tinnitus in hearing loss patients [70].…”
Section: Physicalmentioning
confidence: 99%
“…Having a basic understanding of brain function and anatomical changes is necessary to effectively treat tinnitus. Many treatment modalities have been applied to tinnitus patients, such as repetitive transcranial magnetic stimulation (rTMS) (Poeppl et al, 2018), drug therapy (Zenner et al, 2017), tinnitus counseling and cognitive behavioral therapy (CBT) (Langguth et al, 2013), hearing aids (Yakunina et al, 2019), cochlear implants (Olze, 2015), and tinnitus retraining therapy (Lee et al, 2019). A previous study applied music therapy and observed changes in the GM volume of tinnitus patients; after the Heidelberg model of music therapy intervention, GM volume in the medial superior frontal areas, auditory cortex, and precuneus increased in acute tinnitus patients, accompanied by significantly decreased tinnitus-related distress (Krick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%